The RNA binding protein Sam68 controls T helper 1 differentiation and anti-mycobacterial response through modulation of miR-29 - Volpe, Elisabetta (Cell Death Differ, 2018)
Polarization of naive T cells into interferon (IFN)-γ-producing T helper 1 (Th1) cells is an essential event in the inflammatory response to pathogens. Herein, we identify the RNA binding protein Sam68 as a specific modulator of Th1 differentiation. Sam68-knockout (ko) naive T cells are strongly defective in IL-12-mediated Th1 polarization and express low levels of T-bet and Eomes. Consequently, Sam68-ko Th1 cells are significantly impaired in IFN-γ production. Moreover, we found that Sam68 is required for the induction of an inflammatory Th1 response during Mycobacterium bovis Bacillus Calmette–Guerin (BCG) infection, thus limiting bacterial dissemination in the lungs. Mechanistically, Sam68 directly binds to the microRNA miR-29, a negative regulator of Th1 response, and inhibits its expression during BCG infection. These findings uncover a novel post-transcriptional mechanism required for the Th1-mediated defense against intracellular pathogens and identify a new function for Sam68 in the regulation of the immune response.